Inequality Convergence and Distribution Neutral Fiscal Policy - Sugata Marjit; Amlan Majumder; Sandip Sarkar; Lei Yang (Center for Economic Studies and ifo Institute (CESifo), 2020)
We provide an interesting empirical evidence dealing with the cross country data on equality i.e. movements of Gini coefficient over last four decades. This seems to suggest a robust empirical evidence that the growth or change in inequality across nations has a negative relation with initial degree of inequality. This would imply that poorer nations starting with higher degree of inequality experience weaker growth in inequality, exhibiting some sort of convergence in the inequality generating process. With this evidence as the backdrop we then provide an analytical framework where countries make an effort to neutralize the distributional impact with taxes and transfers that might distort incentives. We prove, under fairly general conditions, that ceteris paribus, lower initial inequality makes it tougher for a country to contain further inequality. Thus cross country inequality is likely to exhibit a converging process.
Keywords: H23; D37; 330; inequality; distribution-neutral; fiscal policy